Rancang Bangun Mekanisme Fess Sebagai Alat Pembanding Pengaruh Geometri Flywheel Terhadap Energi Kinetik Yang Dihasilkan - Adhe Anggry; Yuli Dharta; Andri Wiguna; Armada Armada; Ririn Martasari (Manutech : Jurnal Teknologi Manufaktur, 2016)
Recent days, more and more people are becoming interested in "free-energy". "Free-energy" means the energy sources used freely without to pay. The sources of "free-energy" are sunlight, rainfall, wind energy, wave power, and tidal power. There are other sources of power such as gravity, electrical charge in the atmosphere and ionosphere, and a mass. FESS (Flywheel Energy Storage System) is an attempt to store kinetic energy generated from the rotation flywheel in which the electrical power output from the generator as an input to the motor. Mass flywheel greatly affects the amount of power generated by a generator which will serve as a flywheel device or distributors of energy while at the induction generator to eventually convert mechanical energy into electrical energy and vice versa. In this system design becomes very important for the flywheel can store the kinetic energy. This research aims to design and build mechanisms as a means of comparison FESS flywheel effect of the geometry of the kinetic energy generated. The research method is done by making three different geometric design flywheels, and then analyzed with the help of FESS. From the experimental results, flywheel 1 with a ringtype web-concave generate kinetic energy of 312.30 J and specific energy of 31.23 J / kg, at the flywheel 2 which is type-straight arm kinetic energy gained by 316.73 J and energy specific of 31.67 J / kg and flywheel 3 with a ring-type web-straight kinetic energy obtained by 284.997 J and specific energy of 28.49 J / kg. From the research data we can conclude that each design geometry flywheel has a different contribution to the performance of energy storage.